2017
DOI: 10.1002/prot.25439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of force fields on the conformational and dynamic properties of amyloid β(1‐40) dimer explored by replica exchange molecular dynamics simulations

Abstract: The conformational space and structural ensembles of amyloid beta (Aβ) peptides and their oligomers in solution are inherently disordered and proven to be challenging to study. Optimum force field selection for molecular dynamics (MD) simulations and the biophysical relevance of results are still unknown. We compared the conformational space of the Aβ(1-40) dimers by 300 ns replica exchange MD simulations at physiological temperature (310 K) using: the AMBER-ff99sb-ILDN, AMBER-ff99sb*-ILDN, AMBER-ff99sb-NMR, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 122 publications
(236 reference statements)
1
23
0
Order By: Relevance
“…The dimer structures are classified by cluster analysis and the inter-chain interactions are mainly located in the regions of residues 5-12, 16-23, and 30-40. Another work studied the dimerization of the Aβ polypeptide using REMD, with each replicate lasting for 300 ns (Watts et al, 2018). The analysis of intra-and inter-chain residue distances showed that although the individual chains were highly flexible, the dimeric system stays in a loosely packed antiparallel β-sheet configuration with contacts between two CHC regions.…”
Section: Application Of Enhanced Sampling Methods On Amyloid Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dimer structures are classified by cluster analysis and the inter-chain interactions are mainly located in the regions of residues 5-12, 16-23, and 30-40. Another work studied the dimerization of the Aβ polypeptide using REMD, with each replicate lasting for 300 ns (Watts et al, 2018). The analysis of intra-and inter-chain residue distances showed that although the individual chains were highly flexible, the dimeric system stays in a loosely packed antiparallel β-sheet configuration with contacts between two CHC regions.…”
Section: Application Of Enhanced Sampling Methods On Amyloid Peptidesmentioning
confidence: 99%
“…The results obtained using both the force fields were comparable with the chemical shift values determined by performing NMR experiments. Watts et al (2018) performed an REMD simulation on the Aβ40 dimer using a series of force fields in the AMBER and CHARMM families. The conformational spaces were classified by cluster analysis and projected the energy landscapes in the first 3 dihedral principle components ( Figure 5A).…”
Section: Figure 5 | (A)mentioning
confidence: 99%
“…Chen et al (2018) was corrected to Chen et al (2018a) and Chen et al (2018b) in the reference list after initial online publication.] that define the atoms, residues, and their masses, charges, types, and so on involved in a system under study (Cheng et al, 2018;Couallier, Riaublanc, David, & Rousseau, 2018;Foley, Tessier, & Woods, 2012;Watts, Gregory, Frisbie, & Lovas, 2018). They also include bonded and nonbonded parameters involved in bonded and nonbonded interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The development of force fields, an essential component of MD software, was widely expanded over the years (Table ). Force fields provide parameters that define the atoms, residues, and their masses, charges, types, and so on involved in a system under study (Cheng et al., ; Couallier, Riaublanc, David, & Rousseau, ; Foley, Tessier, & Woods, ; Watts, Gregory, Frisbie, & Lovas, ). They also include bonded and nonbonded parameters involved in bonded and nonbonded interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The lipid mixture (0.55:0.15:0.30 DPPC:DOPC:Chol) is in the liquid-liquid coexistence region of the phase diagram. The protein and lipids were modeled with the CHARMM36 force field (Klauda et al, 2010;Huang et al, 2017;Watts et al, 2018), and the ligand was modeled with the CHARMM general force field (Vanommeslaeghe et al, 2010) with atoms typed by the ParamChem server (Vanommeslaeghe & MacKerell, 2012).…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%